2016
DOI: 10.1139/cjb-2015-0218
|View full text |Cite
|
Sign up to set email alerts
|

Seed-specific overexpression of Arabidopsis DGAT1 in Indian mustard (Brassica juncea) increases seed oil content and seed weight

Abstract: Oil content is an important yield trait in Brassica juncea (L.) Coss. Improvements to yield levels of mustard by conventional breeding methods have reached a plateau. The application of transgenic technology is an area that has not yet been explored for improving the oil content of B. juncea. In this study, the effect of overexpression of AtDGAT1 (a key gene involved in oil biosynthesis) on the seed oil content of B. juncea was investigated. For seed-specific overexpression, the gene was linked to Arabidopsis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…It is well known that the DGAT enzyme catalyzes a rate-limiting reaction in TAG bioassembly, and DGAT1 and DGAT2 genes are responsible for the progress of this reaction 54 . Seed-specific overexpression of AtDGAT1 increased the seed oil content by up to 8.3% in transgenic Brassica juncea as compared to wild type plants 55 . The expression patterns of both XsDGAT1 and XsDGAT2 correlated with oil accumulation in developing Xanthoceras sorbifolia embryos, and overexpression of these genes increased total seed oil content in transgenic plants as compared to wild-type plants 54 .…”
Section: Discussionmentioning
confidence: 94%
“…It is well known that the DGAT enzyme catalyzes a rate-limiting reaction in TAG bioassembly, and DGAT1 and DGAT2 genes are responsible for the progress of this reaction 54 . Seed-specific overexpression of AtDGAT1 increased the seed oil content by up to 8.3% in transgenic Brassica juncea as compared to wild type plants 55 . The expression patterns of both XsDGAT1 and XsDGAT2 correlated with oil accumulation in developing Xanthoceras sorbifolia embryos, and overexpression of these genes increased total seed oil content in transgenic plants as compared to wild-type plants 54 .…”
Section: Discussionmentioning
confidence: 94%
“…The overexpression of T. majus DGAT1 in Arabidopsis, high‐erucic‐acid rapeseed, and canola‐type B. napus also led to enhanced seed oil content (Xu et al, ). Following these aforementioned studies, many groups have further used DGAT1 from different species to boost seed content in various crops such as G. max (Hatanaka et al, ; Roesler et al, ), B. juncea (Savadi et al, ), Z. mays (Alameldin et al, ), C. sativa (Kim et al, ), and Jatropa curcas (Maravi et al, ). Moreover, overexpression of DGAT1 from microalgae, such as Chlorella ellipsoidea and Nannochloropsis oceanica , also led to increased oil content in Arabidopsis and B. napus (Guo et al, ; Zienkiewicz et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of DGAT cDNA in wild-type Arabidopsis seeds increased the oil content by 11–28% [64]. In addition, seed-specific overexpression of AtDGAT1 in Brassica juncea seed improved the oil content significantly, with a maximum oil content increase of 8.3% in the transgenic plants compared to that in the wild-type plants [65]. In addition, we examined the expression profiles of the GPD1 and DGAT1 genes in seeds and berry pulp tissues of one sea buckthorn line, ‘XE3’, and found that these two genes had higher expression in pulp (with an oil content of 36.90%) than in seeds (14.15%) [66].…”
Section: Discussionmentioning
confidence: 99%